People's Republic of China-Hong Kong Special Administrative Region : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
Hong Kong SAR's economy benefitted from a strong cyclical upswing through the first half of 2018, supported by the continued global recovery, buoyant domestic sentiment, and the booming property market. However, near-term risks have significantly increased - including those from trade tensions, tighter global financial conditions, and capital outflows from emerging markets. Also, long-term challenges, including from aging, elevated inequality, and the persistent housing shortage, need to be tackled. Prudent macroeconomic policies and ample buffers are in place to help smoothen the transition and ensure continued stability.